A wide-field suprachoroidal retinal prosthesis is stable and well tolerated following chronic implantation - Villalobos, Joel; Nayagam, David; Allen, Penelope; McKelvie, Penelope; Luu, Chi; Ayton, Lauren; Freemantle, Alexia; McPhedran, Michelle; Basa, Meri; McGowan, Ceara; Shepherd, Robert; Williams, Chris (Association For Research In Vision And Ophthalmology (ARVO), 2013)
Purpose. The safety of chronic implantation of a retinal prosthesis in the suprachoroidal space has not been established. This study aimed to determine the safety of a wide-field suprachoroidal electrode array following chronic implantation using histopathologic techniques and electroretinography. Methods. A platinum electrode array in a wide silicone substrate was implanted unilaterally in the suprachoroidal space in adult cats (n = 7). The lead and connector were tunneled out of the orbit and positioned subcutaneously. Postsurgical recovery was assessed using fundus photography and electroretinography (ERG). Following 3 months of passive implantation, the animals were terminated and the eyes assessed for the pathologic response to implantation. Results. The implant was mechanically stable in the suprachoroidal space during the course of the study. The implanted eye showed a transient increase in ERG response amplitude at 2 weeks, which returned to normal by 3 months. Pigmentary changes were observed at the distal end of the implant, near the optic disc. Histopathologic assessment revealed a largely intact retina and a thin fibrous capsule around the suprachoroidal implant cavity. The foreign body response was minimal, with sporadic presence of macrophages and no active inflammation. All implanted eyes were negative for bacterial or fungal infections. A midgrade granuloma and thick fibrous buildup surrounded the extraocular cable. Scleral closure was maintained in six of seven eyes. There were no staphylomas or choroidal incarceration. Conclusions. A wide-field retinal prosthesis was stable and well tolerated during long-term suprachoroidal implantation in a cat model. The surgical approach was reproducible and overall safe